TGF-β prevents T follicular helper cell accumulation and B cell autoreactivity - McCarron, Mark J. (American Society for Clinical Investigation, 2014)
T follicular helper (Tfh) cells contribute to the establishment of humoral immunity by controlling the delivery of helper signals to activated B cells; however, Tfh development must be restrained, as aberrant accumulation of these cells is associated with positive selection of self-reactive germinal center B cells and autoimmunity in both humans and mice. Here, we show that TGF-β signaling in T cells prevented Tfh cell accumulation, self-reactive B cell activation, and autoantibody production. Using mice with either T cell–specific loss or constitutive activation of TGF-β signaling, we demonstrated that TGF-β signaling is required for the thymic maturation of CD44(+)CD122(+)Ly49(+)CD8(+) regulatory T cells (Tregs), which induce Tfh apoptosis and thus regulate this cell population. Moreover, peripheral Tfh cells escaping TGF-β control were resistant to apoptosis, exhibited high levels of the antiapoptotic protein BCL2, and remained refractory to regulation by CD8(+) Tregs. The unrestrained accumulation of Tfh cells in the absence of TGF-β was dependent on T cell receptor engagement and required B cells. Together, these data indicate that TGF-β signaling restrains Tfh cell accumulation and B cell–associated autoimmunity and thereby controls self-tolerance.